Allergic sensitization and work related asthma among poultry workers in South Africa - Ngajilo, Dorothy (Department of Public Health and Family Medicine, 2017)
Objective: The aim of the study was to determine the risk factors associated with allergic sensitisation and various asthma phenotypes in poultry workers. Methods: A cross-sectional study of 230 currently employed poultry workers used a modified ECRHS questionnaire, spirometry, fractional exhaled nitric oxide, Phadiatop and ImmunoCAP for specific IgE to poultry farming associated allergens (chicken meat, feathers, serum protein, droppings, sunflower seeds, storage mite) and mould mix to investigate workrelated asthma. Results: The mean dust particulate concentration (geometric mean (GM) =11.04mg/m³) was highest in the rearing department while mean (1-3)-ß-D-glucan (GM=148 ng/ m³) and endotoxin levels (GM=2298 EU/m³) were highest in the catching department. Worker's mean age was 37±9 years, 68% were male, 43% current smokers, 34% atopic and 5% casual workers. The prevalence of non-atopic asthma (NAA=10%) was higher than atopic asthma (AA=6%) or probable occupational asthma (OA=5%). Sensitisation to at least one poultry work related allergen was 24%, with sunflower seed and storage mite sensitisation being the most prevalent (13%). In multivariate adjusted models, workers sensitised to chicken specific allergens were more likely to be atopic (OR=20.9, 95% CI: 4.7-93.2) or have casual job status (OR=6.0, 95% CI: 1.1-35.9). Workers with work-related chest symptoms were more likely to work in the rearing department (OR=3.2, 95% CI: 1.2-8.3) and to report episodes of high gas/dust/fume exposures causing asthma symptoms (OR=4.8, 95%CI: 2.4-9.6). Reversible obstructive airway obstruction was more strongly associated with employment in small broiler farms (OR=11.6, 95% CI: 1.0-129.0) as well as casual work (OR=6.4, 95% CI: 1.4-28.0). Furthermore, NAA was strongly associated with casual work (OR=5.0, 95% CI: 1.3-19.0) as well as working in the automated egg laying system (OR=8.0, 95% CI: 1.0-68.6). Further analysis revealed that the proportion of workers sensitised to at least one poultry work related allergen declined with increasing years of service (chi-square trend p=0.023), with workers having <2 years employment demonstrating a higher risk compared to those with >6 years employment (OR=4.0, 95% CI: 1.2-13.8). Conclusion: Non-atopic asthma is the most common asthma phenotype among poultry workers with work in the rearing department demonstrating an increased respiratory risk. The increased risk of reversible airway obstruction among workers in small broiler farms and the declining prevalence of sensitisation with increasing employment duration suggests a healthy worker effect. Preventive measures, including appropriate training, are recommended to reduce respiratory health risks, particularly in novice workers.